1994
DOI: 10.1007/bf01808618
|View full text |Cite
|
Sign up to set email alerts
|

The risk of cancer in relatives of patients with brain neoplasm

Abstract: The family trees of 142 patients, suffering from histologically proven brain tumour, were compared to those of an equal number of sex and age matched controls. The results showed no statistically significant differences in the occurrence of malignant neoplasm between the two groups. These results indicate that the risk of cancer among relatives of patients with brain tumours does not exceed that of healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Previous registry and case control studies have found an elevated risk for specific cancers particularly nervous system cancers (Hemminki et al, 2000, 2001; Malmer et al, 2003), or family history of cancer in first-degree relatives of persons with meningioma (Hill et al, 2004). A family study conducted by Sakas et al (1994) found no significant difference in family history of cancer between persons with benign or malignant brain neoplasms and healthy controls. Our population reported relatively high rates of nervous system cancers in first and second-degree relatives, compared to previous studies that have suggested elevated standard incidence ratios for nervous systems in first-degree family members of persons with meningioma (Hemminki and Li, 2004).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous registry and case control studies have found an elevated risk for specific cancers particularly nervous system cancers (Hemminki et al, 2000, 2001; Malmer et al, 2003), or family history of cancer in first-degree relatives of persons with meningioma (Hill et al, 2004). A family study conducted by Sakas et al (1994) found no significant difference in family history of cancer between persons with benign or malignant brain neoplasms and healthy controls. Our population reported relatively high rates of nervous system cancers in first and second-degree relatives, compared to previous studies that have suggested elevated standard incidence ratios for nervous systems in first-degree family members of persons with meningioma (Hemminki and Li, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Though the sample size of this analysis is considerable considering the rarity of brain tumors, the small sample size results in some instability of the data produced by the analysis. Previous studies that have examined the relationship between family history and brain tumors have been based on populations between 3239 and 11,875 in registry-based studies (Malmer et al, 2003; Hemminki et al, 2007), 96 in case control studies (Hill et al, 2004), and 142 in family-based studies (Sakas et al, 1994). Previous studies examining the relationship between family history of cancer and glioma have been based on populations between 462 and 489 in case control studies (Wrensch et al, 1997; Hill et al, 2003), 20358 in registry-based studies (Malmer et al, 2003), and between 639 and 1476 in family-based studies (de Andrade et al, 2001; Scheurer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation